1976
DOI: 10.1007/bf02906537
|View full text |Cite
|
Sign up to set email alerts
|

Properties and morphology of barley embryo acetyl CoA carboxylase

Abstract: Acetyl CoA carboxylase was isolated and purified from barley embryos. The purified enzyme fixed CO2 at the rate of 7 to 7.4 lamoles per min per mg protein. It had a molecular weight of 610 000 daltons and one mole of biotin per mole of enzyme. The purified enzyme aggregates during sepharose 6 B gel filtration. Aggregation of the enzyme can be prevented by using i% sodium chloride in the elution buffer. The biotin carboxyl carrier protein of the enzyme was identified as a small polypeptide with a molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The enzyme activities of the whole tissue homogenate ofembryo isolates from 1-day seedlings (Table I) are comparable to those reported for wheat germ (13) and barley embryo extracts (6). The increased activity during development (Table I) (31) on studies with developing leaves of Chl-deficient barley mutants were in agreement with this in that the enzyme activities of the mutants they studied remained below those of the wild type.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The enzyme activities of the whole tissue homogenate ofembryo isolates from 1-day seedlings (Table I) are comparable to those reported for wheat germ (13) and barley embryo extracts (6). The increased activity during development (Table I) (31) on studies with developing leaves of Chl-deficient barley mutants were in agreement with this in that the enzyme activities of the mutants they studied remained below those of the wild type.…”
Section: Discussionsupporting
confidence: 80%
“…Biotin estimations as performed were presumed adequate for the ted 3 mi with localization of the acetyl-CoA carboxylase because it is the only C03 then was biotin enzyme described for plants. The biotin levels of 1.0 to 3.1 pg/mg protein (Table IX) exceed those reported for purified barley-embryo acetyl-CoA carboxylase (6); however, they are somewhat less than the biotin content of purified BCCP (6,10). The high readings obtained probably reflect a high free-biotin content in the chloroplast stromal preparations.…”
Section: 495mentioning
confidence: 53%
See 1 more Smart Citation
“…Although the subunit size in animals, yeast and plants is > 200 kDa there have been reports of much smaller (50,60 or 75 kDa) subunits being present in certain plant tissues [6,20,[32][33][34][35][36][37]46]. In animals the enzyme exists in the cytoplasm and is subject to complex regulatory mechanisms including multi-site phosphorylation [12].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of plant acetyl-CoA carboxylases is unclear since acetyl-CoA carboxylases with biotin-containing subunits, ranging from 21 to 240 kDa, have been reported (67)(68)(69)(70)(71)(72)(73)(74)(75)(76). A number of studies have reported the purification of acetyl-CoA carboxylases containing a large, 220 kDa, biotin-containing subunit (74)(75)(76).…”
Section: Properties Of Plant Biotin-containing Enzymesmentioning
confidence: 99%